2020
DOI: 10.3390/ijms21249711
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Self-Association Studies of Beta-Lactoglobulin

Abstract: The aim of this study was to investigate isolated β-lactoglobulin (β-LG) from the whey protein isolate (WPI) solution using the column chromatography with SP Sephadex. The physicochemical characterization (self-association, the pH stability in various salt solutions, the identification of oligomeric forms) of the protein obtained have been carried out. The electrophoretically pure β-LG fraction was obtained at pH 4.8. The fraction was characterized by the matrix-assisted laser desorption ionization-time of fli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 81 publications
2
18
0
Order By: Relevance
“…For instance, for A-type lipase of Candida antarctica pI value at 4 was determined by electrophoretic mobility, whereas the isoelectric focusing technique showed the pI value as 7.5 (Salgın et al, 2012). Moreover, the studies performed in our group have shown that depending on the ions present in the solution the determined pI values for β-LG were from 5.3 to 7.6 within the same technique (Gołębiowski et al, 2020). The study indicates the high importance of the effect of specific proteinion interactions on the obtained results.…”
Section: Interactions Between Bltf and Zincmentioning
confidence: 61%
“…For instance, for A-type lipase of Candida antarctica pI value at 4 was determined by electrophoretic mobility, whereas the isoelectric focusing technique showed the pI value as 7.5 (Salgın et al, 2012). Moreover, the studies performed in our group have shown that depending on the ions present in the solution the determined pI values for β-LG were from 5.3 to 7.6 within the same technique (Gołębiowski et al, 2020). The study indicates the high importance of the effect of specific proteinion interactions on the obtained results.…”
Section: Interactions Between Bltf and Zincmentioning
confidence: 61%
“…Figure 5 shows that there is a moderate increase in the β-Lg negative charge with a pH value rise from 5.2 to 8.5. Unfortunately, contrary to lower pH values where the protein is present in a monomeric form, the dimeric form predominantly occurs in the discussed pH range, 28 resulting in a significantly different size and also surface charge distribution. For this reason, any differences in the retention trend could not be attributed solely to a change of interaction strength, but structural changes must also be considered, making a correct interpretation challenging.…”
Section: Resultsmentioning
confidence: 95%
“… 26 More importantly, it has a high dipole moment 27 and a broad isoelectric point between 4.8 and 5.9. 28 This enables retention on an anion and cation exchange column at certain mobile phase pH values within this range. The same conditions in the mobile phase and the same pressure (same standard partial molar volume in the mobile phase and charge distribution) enabled the study of the change in the retention time trend with pressure solely due to the differences in the adsorption processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These values are obtained using the multi-angle light scattering (MALS) technique. Determining the radius of gyration, as well as the molar mass distribution of biocolloids and biopolymers, is an important issue in the field of physicochemical description of nanoparticles [29][30][31]. The applied analytical method allowed us to obtain ZnO particle size values before and after immobilization with ampicillin and tetracycline.…”
Section: Physico-chemical Characteristics Of Immobilized Zinc Oxide Nanoparticlesmentioning
confidence: 99%